Measurement of the efficiency of monetary policy - Eka Purwanda; Siti Herni Rochana (Economic Journal of Emerging Markets, 2017)
Since 2000, monetary policy in Indonesia started to use Inflation Targeting Framework (ITF). To evaluate the performance of the monetary policy, it requires efficiency indicators. The measurement of the efficiency of monetary policy is based on inflation and output variations. This paper formulates a method for measuring the efficiency of monetary policy and applies it in Indonesia. It finds that since the implementation of ITF, the efficiency of monetary policy has not changed significantly. However, the efficiency of monetary policy tends to increase after the full implementation of the ITF framework after 2005 than in the transition period of 2000-2005.